2019
DOI: 10.1002/nadc.20194083853
|View full text |Cite
|
Sign up to set email alerts
|

Die Natur als Labor – Chemieunterricht im Freiland

Abstract: Abstract„Natur statt Chemie“, „Chemiefreies Leben“, „Stark ohne Chemie“, die Liste an diesen aus der Werbung entnommenen Slogans ließe sich beliebig erweitern. Doch Chemie kommt überall vor, erst recht in der Natur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In total, more than a quarter (28.3%) of the interviewees indicate to read the references to learn more about the fragrances in a certain product. Overall, more men, especially young men (age class [18][19][20][21][22][23][24], than women read the references (Fig. 3).…”
Section: Knowledge: Wrong Assumptions About Fragrances Are Frequentmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, more than a quarter (28.3%) of the interviewees indicate to read the references to learn more about the fragrances in a certain product. Overall, more men, especially young men (age class [18][19][20][21][22][23][24], than women read the references (Fig. 3).…”
Section: Knowledge: Wrong Assumptions About Fragrances Are Frequentmentioning
confidence: 99%
“…The positive attitude toward these trigger words is widespread in the general population [10], although toxicity of "green" and natural products is similar to regular products [1,20]. This uncritical opinion about natural substances can also be explained by the widespread infantilization and naïve view on nature in today's society, especially in the young generation, suitably called "Bambi syndrome" [23]. The survey conducted in Germany in 2010 revealed that people with lower income had a more positive attitude toward products called "natural" and more critical attitude toward chemicals in general, while, surprisingly, the education did not seem to play any role for this attitude [10].…”
Section: Exposure: People Who Report Adverse Health Effects From Fragmentioning
confidence: 99%